The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1371/journal.pone.0218300
|View full text |Cite
|
Sign up to set email alerts
|

The Dps4 from Nostoc punctiforme ATCC 29133 is a member of His-type FOC containing Dps protein class that can be broadly found among cyanobacteria

Abstract: Dps proteins (DNA-binding proteins from starved cells) have been found to detoxify H 2 O 2 . At their catalytic centers, the ferroxidase center (FOC), Dps proteins utilize Fe 2+ to reduce H 2 O 2 and therefore play an essential role in the protection against oxidative stress and maintaining iron homeostasis. Whereas most bacteria accommodate one or two Dps, there are five different Dps proteins in… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 74 publications
0
9
0
Order By: Relevance
“…The protein Dps4 from Nostoc punctiforme (NpDps4) (PDB ID code 5hjf) ( 41 ) meets all the above criteria ( Fig. 2 B ).…”
Section: Resultsmentioning
confidence: 99%
“…The protein Dps4 from Nostoc punctiforme (NpDps4) (PDB ID code 5hjf) ( 41 ) meets all the above criteria ( Fig. 2 B ).…”
Section: Resultsmentioning
confidence: 99%
“…Compared with the sequences of conventional Dps proteins, TlDps1 possesses unique amino acids including Phe52, His78, and His164, which are characteristic of Dps proteins with His-type FOCs as previously isolated from the cyanobacteria T. elongatus and N. punctiforme [6,7]. A sequence similarity search illustrated that TlDps1 shares 66% and 70% sequence identity with the His-type FOC-containing proteins TeDpsA and NpDps4, respectively, whereas it shares low sequence identities with conventional Dps proteins from bacteria such as Escherichia coli (EcDps, 27%), Listeria innocua (LiDps, 27%), Mycobacterium smegmatis (MsDps1, 28%), Deinococcus radiodurans (DrDps1, 28%), and T. elongatus (TeDps, 30%).…”
Section: Identification Of Tldps1mentioning
confidence: 99%
“…FOCs catalyze the oxidative conversion of Fe 2+ to Fe 3+ using O 2 and/or H 2 O 2 to protect DNA from oxidative damage caused by the Fenton reaction, and Dps proteins take up Fe cations within the cavity through pores [5]. Because FOCs have a crucial role in cell survival under oxidative stresses, the DNA-binding and iron uptake ability of Dps proteins together with crystal structures of FOCs from various types of bacteria have been revealed [3,[6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24]. Conventional FOCs in Dps proteins consist of highly conserved amino acids, including two His, one Trp, one Asp, and one Glu residue, and two Fe cations are coordinated to these amino acid residues.…”
mentioning
confidence: 99%
“…The ligation of the ferroxidase center in this protein differs markedly from canonical Dps proteins and closely resembles that of bacterial Bfrs discussed above ( 191 ). Finally, NpDps4 possesses unusually His-rich ligation of iron at the ferroxidase center and utilizes only O 2 and not H 2 O 2 as an oxidant for iron ( 198 ). Accordingly, a role for this protein has been proposed as an O 2 scavenger within heterocysts where nitrogenase activity requires that a microoxic (<10 μ m O 2 ) environment be maintained ( 199 ).…”
Section: Iron Storage In Bacteriamentioning
confidence: 99%
“…Accordingly, a role for this protein has been proposed as an O 2 scavenger within heterocysts where nitrogenase activity requires that a microoxic (<10 μ m O 2 ) environment be maintained ( 199 ). Based on sequence comparisons with other Dps proteins, it has been suggested that this type of reaction center, which is common among, but restricted to, the cyanobacteria ( 198 ) be classified as the His-type ferroxidase center.…”
Section: Iron Storage In Bacteriamentioning
confidence: 99%